Assessing the water quality in the Timbalun river watershed, Padang City, West Sumatra, Indonesia - HAR, RUSLI; TANJUNG, DENNY AKBAR; JAMARUN, NOVESAR (Universitas Syiah Kuala, 2025)
The purpose of this study is to assess water quality, specifically pH, conductivity, total dissolved solids (TDS), salinity, and turbidity. The research utilizes quantitative methods and covers 15 sampling points across the Timbalun River basin in Padang City, West Sumatra, Indonesia. Samples were measured based on several parameters, with three repetitions for accuracy. The testing took place from August to September 2024. The results showed that some water quality parameters, such as pH and total dissolved solids, met the standards outlined by Ministry of Health Regulation No. 2 of 2023. However, other parameters, including salinity, conductivity, and turbidity, did not meet the specified thresholds. It is essential to implement treatment measures to ensure the water meets the required standards for its intended use.